Luftwaffe eagle : a WWII German airman's story - Sommer, Erich, 1912-2005 (Grub Street, 2018)
In this compelling memoir, Erich Sommer recalls his life in pre-war Germany and the adventures he had flying for the Luftwaffe during the Second World War. Born in 1912, the third son of a district court judge, Erich grew up in an atmosphere of uncertainty following the First World War. In 1932 he started training as a brewery engineer, shortly afterwards the Nazis came to power. The implications this had on the lives of average Germans are described in great detail.